please help out with this integration question
Attachments:
![](https://hi-static.z-dn.net/files/d26/87c202e1aa47265cea4cb1e19a724a93.jpg)
Swarup1998:
fof (3) ?
Answers
Answered by
11
Question :
If f (x) =
and g (x) = x² + 7, find fog (3), fog (-3), gof (2) and fof (-3)
Solution :
Given, f (x) =![\frac{3x+5}{7x+2} \frac{3x+5}{7x+2}](https://tex.z-dn.net/?f=%5Cfrac%7B3x%2B5%7D%7B7x%2B2%7D)
g (x) = x² + 7
So, g (3) = 3² + 7 = 9 + 7 = 16
Now, fog (3)
= f (g (3))
= f (16)
=![\frac{3(16)+5}{7(16)+2} \frac{3(16)+5}{7(16)+2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%2816%29%2B5%7D%7B7%2816%29%2B2%7D)
=![\frac{48+5}{112+2} \frac{48+5}{112+2}](https://tex.z-dn.net/?f=%5Cfrac%7B48%2B5%7D%7B112%2B2%7D)
=![\frac{53}{114} \frac{53}{114}](https://tex.z-dn.net/?f=%5Cfrac%7B53%7D%7B114%7D)
Also, g (-3) = (-3)² + 7 = 9 + 7 = 16
Since, g (3) = g (-3), we can say that
fog (-3) = fog (3) =![\frac{53}{114} \frac{53}{114}](https://tex.z-dn.net/?f=%5Cfrac%7B53%7D%7B114%7D)
Now, f (2)
=![\frac{3(2)+5}{7(2)+2} \frac{3(2)+5}{7(2)+2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%282%29%2B5%7D%7B7%282%29%2B2%7D)
=![\frac{6+5}{14+2} \frac{6+5}{14+2}](https://tex.z-dn.net/?f=%5Cfrac%7B6%2B5%7D%7B14%2B2%7D)
=![\frac{11}{16} \frac{11}{16}](https://tex.z-dn.net/?f=%5Cfrac%7B11%7D%7B16%7D)
Now, gof (2)
= g (f (2))
= g (
)
=![(\frac{11}{16})^{2}+7 (\frac{11}{16})^{2}+7](https://tex.z-dn.net/?f=%28%5Cfrac%7B11%7D%7B16%7D%29%5E%7B2%7D%2B7+)
=![\frac{121}{256}+7 \frac{121}{256}+7](https://tex.z-dn.net/?f=%5Cfrac%7B121%7D%7B256%7D%2B7+)
=![\frac{121+1792}{256} \frac{121+1792}{256}](https://tex.z-dn.net/?f=%5Cfrac%7B121%2B1792%7D%7B256%7D)
=![\frac{1913}{256} \frac{1913}{256}](https://tex.z-dn.net/?f=%5Cfrac%7B1913%7D%7B256%7D)
Now, f (-3)
=![\frac{3 (-3)+5}{7 (-3)+2} \frac{3 (-3)+5}{7 (-3)+2}](https://tex.z-dn.net/?f=%5Cfrac%7B3+%28-3%29%2B5%7D%7B7+%28-3%29%2B2%7D)
=![\frac{-9+5}{-21+2} \frac{-9+5}{-21+2}](https://tex.z-dn.net/?f=%5Cfrac%7B-9%2B5%7D%7B-21%2B2%7D)
=![\frac{-4}{-19} \frac{-4}{-19}](https://tex.z-dn.net/?f=%5Cfrac%7B-4%7D%7B-19%7D)
=![\frac{4}{19} \frac{4}{19}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B19%7D)
So, fof (-3)
= f (f (-3))
= f (
)
=![\dfrac{3(\frac{4}{19})+5}{7(\frac{4}{19})+2} \dfrac{3(\frac{4}{19})+5}{7(\frac{4}{19})+2}](https://tex.z-dn.net/?f=%5Cdfrac%7B3%28%5Cfrac%7B4%7D%7B19%7D%29%2B5%7D%7B7%28%5Cfrac%7B4%7D%7B19%7D%29%2B2%7D)
=![\dfrac{\frac{12}{19}+5}{\frac{28}{19}+2} \dfrac{\frac{12}{19}+5}{\frac{28}{19}+2}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cfrac%7B12%7D%7B19%7D%2B5%7D%7B%5Cfrac%7B28%7D%7B19%7D%2B2%7D)
=![\frac{12+95}{28+38} \frac{12+95}{28+38}](https://tex.z-dn.net/?f=%5Cfrac%7B12%2B95%7D%7B28%2B38%7D)
=
If f (x) =
Solution :
Given, f (x) =
g (x) = x² + 7
So, g (3) = 3² + 7 = 9 + 7 = 16
Now, fog (3)
= f (g (3))
= f (16)
=
=
=
Also, g (-3) = (-3)² + 7 = 9 + 7 = 16
Since, g (3) = g (-3), we can say that
fog (-3) = fog (3) =
Now, f (2)
=
=
=
Now, gof (2)
= g (f (2))
= g (
=
=
=
=
Now, f (-3)
=
=
=
=
So, fof (-3)
= f (f (-3))
= f (
=
=
=
=
Answered by
12
Answer: fog(-3) = 107/66 and gof(2) = 1913/256
Step-by-step explanation:
We have,
f(x) = (3x+5)/(7x+2
g(x) = x² +7
Now,
f(-3) = [3*(-3)+5]/[7*(-3)+2]
= (-9+5)/(-21+2)
= -4/-19
= 4/19
fof(-3) = f(f(-3))
= f(4/19)
fof(-3) = 107/66
f(2) = [3*2+5]/[7*2+2]
= (6+5)/(14+2)
= 11/16
g(11/16) = (11/16)² +1
= 121/256 + 7
= (121+1792)/256
= 1913/256
gof(2) = g(f(2))
= g(11/16)
gof(2) = 1913/256
Similar questions